2018
DOI: 10.1111/bjep.12231
|View full text |Cite
|
Sign up to set email alerts
|

Teaching assistant and pupil interactions: The role of repair and topic management in scaffolding learning

Abstract: Teaching assistants require training in scaffolding as an instructional strategy, and educational psychologists (EPs) could play a vital role in this respect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…Elsewhere, analyses by Rubie-Davies, Blatchford, Webster, Koutsoubou, and Bassett (2010) found that TAs are more concerned with task completion and correction than learning. Similar issues have been found in literacy intervention ses sions led by TAs (Bosanquet & Radford, 2018).…”
Section: If Pupil Factors Cannot Explain the Negative Relationship Be...supporting
confidence: 68%
“…Elsewhere, analyses by Rubie-Davies, Blatchford, Webster, Koutsoubou, and Bassett (2010) found that TAs are more concerned with task completion and correction than learning. Similar issues have been found in literacy intervention ses sions led by TAs (Bosanquet & Radford, 2018).…”
Section: If Pupil Factors Cannot Explain the Negative Relationship Be...supporting
confidence: 68%
“…In addition to that, the provision of additional support for teachers and students such as teaching assistants or temporary/permanent team teaching should be reviewed. In this context, not only teaching assistants' or additional teachers' frequency of their presence and work in the classroom should be investigated, but also their role when being present which can have an significant impact on teachers' pedagogical decision making and students' perception and experience of classroom processes (Radford et al, 2015;Wren, 2017;Bosanquet and Radford, 2019). Interestingly, in classes with a higher number of female students, profile 2 is more common compared to profile 3.…”
Section: Discussionmentioning
confidence: 99%
“…TAs have been deployed to facilitate inclusion for children with SEND and as an informal instructional resource for pupils in need (Sharples, Webster, and Blatchford 2018). Concerns raised as TAs take on these responsibilities include inadequate preparation and training (Sharples, Webster, and Blatchford 2018;Bosanquet and Radford 2019); individual attention and support for pupils with SEND potentially leading to lack of progress and less inclusive opportunities (Webster et al 2010). The Deployment and Impact of Support Staff (DISS) project examined TA support for pupils with SEND (Webster et al 2010) and revealed such unintentional consequences as greater separation from teachers and the curriculum as a result of missed opportunities, due mainly to separate workstations, and limited inclusive experiences for some children.…”
Section: Teaching Assistantsmentioning
confidence: 99%